Nitrogen and Sulfur Fertilization Effects on Camelina Sativa in West Central Kansas - E. Obeng; A. Obour (Kansas Agricultural Experiment Station Research Reports, 2015)
Camelina sativais early maturing and possesses characteristics that make it a good fit as a rotation crop in dryland wheat cropping systems. Nitrogen (N) and sulfur (S) play very important roles in oilseed production, including camelina. This study was undertaken in 2013 and 2014 to determine N and S rates necessary for optimum camelina production in West Central Kansas. The experiment was set up as randomized complete blocks with four replications in a split-plot arrangement. Treatments were two S rates (0 and 18 lb/a) as the main plots, and N rates (0, 20, 40, and 80 lb/a) were the subplots. The results showed that plant stand, plant height, harvest index, biomass yield, and protein and oil content were unaffected by N and S application. Similarly, S application had no effect on seed yield. However, N rate had a significant (P<0.05) effect on seed yield. Yield differences were realized for 2013 (~450 lb/a) and 2014 (~900 lb/a).
Keywords: camelina; nitrogen; sulfur